2021
DOI: 10.1111/1365-2745.13588
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting responses of different functional groups stabilize community responses to a dominant shrub under global change

Abstract: Changes in precipitation regimes and nitrogen deposition levels due to global change are altering terrestrial ecosystems worldwide. Most attempts at understanding how biotic interactions affect plant species and community responses to global change have focused on biotic interactions measured at the community level. However, these approaches ignore that communities include functionally dissimilar species that might respond differently to changes in the effects of dominant neighbours along environmental gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 125 publications
(175 reference statements)
0
8
0
1
Order By: Relevance
“…This result highlights that communities are complex units of interacting species from different functional strategies (Michalet et al, 2015a). This finding is key since balancing within‐community responses to environmental conditions and effects of neighbours may stabilize community responses to climate change, as shown by Bai et al (2021) in continental dune communities of North China.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…This result highlights that communities are complex units of interacting species from different functional strategies (Michalet et al, 2015a). This finding is key since balancing within‐community responses to environmental conditions and effects of neighbours may stabilize community responses to climate change, as shown by Bai et al (2021) in continental dune communities of North China.…”
Section: Discussionmentioning
confidence: 73%
“…This result highlights that communities are complex units of interacting species from different functional strategies(Michalet et al, 2015a). This finding is key since balancing within-community responses to environmental conditions and effects of neighbours may stabilize community responses to climate change, as shown byBai et al (2021) in continental dune communities of North China.Consistent with our third hypothesis, and the results of several authors(Michalet et al, 2015a;Wang et al, 2017), we found that the different responses of subordinate species to the shrub's effects were significantly related to community composition, as shown by variation in the relative frequency and abundance of group A and group B between the intact-shrub and shrub-removed and open treatments. Thus, balancing responses of different species groups at the community level may contribute to explaining community composition.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…However, the increased MAT increased the rhododendron andpotentilla effects and decreased the salix effect on the homogenization of nematode communities. A possible explanation was the differences in shrub crown diameter, which was related to litter inputs and was recognized as a good proxy of shrub competitive ability and influence range (Zhang et al , 2020;Bai et al , 2021). Compared with other shrubs, salix had the largest crown diameter, and its crown diameter increased significantly with MAP (Figure S6, Figure S7d).…”
Section: Mat and Map Alter Shrub Effects On Beta Diversity Of Nematod...mentioning
confidence: 99%
“…Through niche differentiation of roots, below-ground resources such as soil water and nutrients can be fully utilized, which is not only conducive to the coexistence of species but also enables them to cope with environmental changes (Schwinning & Ehleringer, 2001;Tiemuerbieke et al, 2018). Moreover, a recent study reported that functional differences between species groups and plant-plant interactions stabilize community responses to global change scenarios such as increased precipitation (Bai et al, 2021).…”
Section: Interactions Between Extreme Precipitation and Sand Dune Slope Positionsmentioning
confidence: 99%